Rapid and Visual Detection of SARS-CoV-2 Using Multiplex Reverse Transcription Loop-Mediated Isothermal Amplification Linked With Gold Nanoparticle-Based Lateral Flow Biosensor - Chen, Xu; Zhou, Qingxue; Li, Shijun; Yan, Hao; Chang, Bingcheng; Wang, Yuexia; Dong, Shilei (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus that causes the outbreak of coronavirus disease 2019 (COVID-2019) all over the world. In the absence of appropriate antiviral drugs or vaccines, developing a reliable, simple, and rapid assay for SARS-CoV-2 is necessary for the prevention and control of the COVID-19 transmission. Methods: A novel molecular diagnosis technique, named multiplex reverse transcription loop-mediated isothermal amplification linked to a nanoparticle-based lateral flow biosensor (mRT-LAMP-LFB), was applied to detect SARS-CoV-2 based on the SARS-CoV-2 RdRp and N genes, and the mRT-LAMP products were analyzed using nanoparticle-based lateral flow biosensor. The mRT-LAMP-LFB amplification conditions, including the target RNA concentration, amplification temperature and time were optimized. The sensitivity and specificity of the mRT-LAMP-LFB method were tested in the current study, and the mRT-LAMP-LFB assay was applied to detect the SARS-CoV-2 virus from clinical samples and artificial sputum samples. Results: The SARS-CoV-2 specific primers based on the RdRp and N genes were valid for establishment of mRT-LAMP-LFB assay to detect SARS-CoV-2 virus. The multiple-RT-LAMP amplification condition was optimized at 63℃ for 30 min. The full process, including reaction preparation, viral RNA extraction, RT-LAMP, and product identification, could be achieved in 80 min. The limit of detection (LoD) of the mRT-LAMP-LFB technology was 20 copies per reaction. The specificity of mRT-LAMP-LFB detection was one hundred percent, and no cross-reactions to other respiratory pathogens were observed. Conclusion: The mRT-LAMP-LFB technique developed in current study is a reliable, rapid, simple, specific and sensitive method to identify SARS-CoV-2 virus for prevention and control of the COVID-19 disease, especially in resource-constrained regions of the world.